Active listening : building skills for understanding : teacher's edition - Helgesen, Marc.; Brown, Steven (Cambridge [England] : New York, NY : Cambridge University Press, 1994)
This book helps students listen for gist and specific information, to make inferences and to progress to content-based activities.
Keywords: Listening -- Study and teaching; Listening -- Problems, exercises, etc; Active learning